Management of Fusarium wilt of strawberry. (July 2015) - Koike, Steven T.; Gordon, Thomas R.
Abstract: Fusarium wilt of strawberry was first described in the 1960s in Australia and Japan. Since then the pathogen, Fusarium oxysporum f. sp. fragariae (Fof), has been reported worldwide with the majority of cases being found in the 1990s and 2000s. Many of these recent reports are associated with changes in pre-plant soil fumigation practices. The disease is of significant economic importance because infected plants can collapse and die. Field diagnosis of Fusarium wilt is complicated by the fact that other soilborne diseases exhibit very similar symptoms. Methods for detection of Fof based on molecular criteria have been developed, but none have yet been shown to uniquely identify the strain of F. oxysporum causing Fusarium wilt of strawberry. Management of Fusarium wilt is best achieved through the use of resistant strawberry cultivars. Research indicates that sources of Fof resistance exist in strawberry germplasm, though cultivar reactions may differ depending on the Fof isolate. Pre-plant treatment of infested soil with fumigants remains a useful management tool. In addition, alternative treatments such as steam, solarization, anaerobic soil disinfestation, and the planting of brassicaceae crops are being assessed for their effectiveness in managing the disease. Standard integrated pest management practices of crop rotation with non-hosts, planting of pathogen-free transplants, and sanitation of equipment remain important measures that can reduce the risk of damage from Fusarium wilt.